2011
DOI: 10.1142/s0218127411028982
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Lifespan Metric of Reading Fluency

Abstract: Much evidence suggests complexity in cognitive and motor task performances [Gilden, 2001]. The present study builds upon this work, treating reading of text as a kind of complex coordination or coupling between reader and reading conditions. Three self-paced reading conditions presented connect text in units of different sizes: word, phrase, or sentence units, and repeatedly measure times between spacebar presses to advance the text. The three conditions reveal different patterns across the data. These pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Wallot & Van Orden (2011b), found a similar outcome using phrase-unit presentations. Reading times to sentence units are rate limiting compared to spacebar pressing, which is not true of reading times to word units, and so sentences allow the more telling portrait of reading performance.…”
Section: Cross-recurrence Quanti Cation Analysismentioning
confidence: 62%
“…Wallot & Van Orden (2011b), found a similar outcome using phrase-unit presentations. Reading times to sentence units are rate limiting compared to spacebar pressing, which is not true of reading times to word units, and so sentences allow the more telling portrait of reading performance.…”
Section: Cross-recurrence Quanti Cation Analysismentioning
confidence: 62%
“…Wallot and Van Orden used these methods to analyze the variability, stability and interconnectedness of reading performance in a self-paced reading task, where participants reveal every new piece of text with a button press [18], [19], [20]. Could show that the reading dynamics of longer text chunks (i.e., sentences) were much more informative compared to shorter text chunks (i.e., individual words) that are commonly used in self-paced reading tasks [18], [20]. Furthermore, they found that nonlinear statistics were more sensitive in distinguishing between more and less fluent readers [20].…”
Section: Reading and Text Readingmentioning
confidence: 99%
“…Could show that the reading dynamics of longer text chunks (i.e., sentences) were much more informative compared to shorter text chunks (i.e., individual words) that are commonly used in self-paced reading tasks [18], [20]. Furthermore, they found that nonlinear statistics were more sensitive in distinguishing between more and less fluent readers [20]. These first results motivate a more thorough comparison of more traditional and nonlinear metric of the text reading process.…”
Section: Reading and Text Readingmentioning
confidence: 99%
“…Holden, 2002; Holden et al, 2009; Wallot & Van Orden, 2011b). This prediction aligns with the many recent findings across human physiology and cognition that reveal less clear 1/ f scaling in less coordinated, less fluent processes.…”
Section: Hypothesismentioning
confidence: 99%